EFEKTIFITAS PEMBERIAN JUS TOMAT DITAMBAH JERUK NIPIS TERHADAP TEKANAN DARAH PADA WANITA DEWASA - Hidayah, Nur; Ambarwati, Ria (JURNAL RISET GIZI, 2017)
Background : Treatment of hypertension in the long term can affect adherence and cause toxic effects, therefore it takes alternative treatment by utilizing nutrients in food, one of which is the antioxidant like as lycopene and flavonoid in tomato-lime juice.Objective : The aim of this study was to analyze the effect of tomato juicewith extra lime on blood pressure in women adults.Methods : This study was clinical nutrition research with True Experiment randomized repeated measure control group design. The subject were 39 women adult 40-60 years, 19 control groups and 20 in treatment. Intervention was performed for 21 days with the measurement of systolic and diastolic blood pressure every 1 week 1 time. The statistical analysis was done by Anova Repeated Measure test with 95% confidence degree.Results : Anova Repeated Measure show that tomato juice with extra limecan lowered systolic and diastolic blood pressure (Î± = 0.005, p = 0.002 and p = 0.038), while the level of energy, protein, fat, carbohydrate, fiber, sodium, and potassium did not affect in systolic and diastolic blood pressure.Conclusion : tomato-lime juice effectively lowered systolic and diastolic blood pressure.